THE RELATIONSHIP BETWEEN KNOWLEDGE AND COMPLIANCE WITH FE TABLET CONSUMPTION WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN AT THE KABANJAHE HEALTH CENTER, KABANJAHE SUB-DISTRICT, KARO DISTRICT KARO YEAR 2023 - Rosma Juita Sibarani; Eva Ratna Dewi; Mastaida Tambun; Manurung, Basaria; Petra Dian Sari Zega; Manalu, Insawani (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
World Health Organization (WHO) in 2014 the Maternal Mortality Rate (MMR) in the world was 289,000. The number of maternal deaths decreased from 385 in 1990 to 216 in 2015 per 100,000 live births. the prevalence of anemia in pregnant women in the world is around 40.1 percent. The percentage has increased from 2015 by 39.8 percent and 2014 by 39.6 percent (WHO, 2016).Objectives of the study: The purpose of this study was to analyze the relationship between knowledge and compliance of Fe tablet consumption with the incidence of anemia in pregnant women at the Kabanjahe Health Center, Kabanjahe District, Karo Regency in 2023. analytical survey research using a cross sectional study to study the influence between the independent variable and the dependent variable through hypothesis testing. The population of this study were pregnant women at the Kabanjahe Health Center, Kabanjahe District, Karo Regency in 2023 as many as 46 people, total sampling determined the number of samples according to the needs of the study The results of statistical tests with a p value = 0.011 mean that there is a significant relationship between parity on the incidence of anemia in pregnant women. the results of statistical tests with a p value = 0.007 mean that there is a significant relationship between knowledge on the incidence of anemia in pregnant women. the results of the study of the variable adherence to Fe tablet consumption on the incidence of anemia in pregnant women obtained statistical test results with a p value = 0.000, meaning that there is a significant relationship between adherence to Fe tablet consumption on the incidence of anemia in pregnant women. Can be a source of information, motivation for health services and midwives against the incidence of anemia in pregnant women.